Economic Aspects of Termination of War Contracts - Nemmers, Erwin Esser (Quarterly Journal of Economics, 1945)
Nature and scope of the problem, 386. — Announced objectives of terminations, 388. — Implementation of legislative objectives, 389. — Statistics of terminations, 392. — Effect of practices on stated objectives, 394. — The economics in action, 397. — The contributions of economics, 400. — Conclusion, 404.